Associations and autoimmunity in hypothyroidism among the pregnant ladies attending a tertiary care hospital of Bangladesh - Mita Dutta; Mohammad Aminul Islam; Faria Afsana; Md Feroz Amin; Md Faruque Pathan (BIRDEM Medical Journal, 2024)
Background: Autoimmune hypothyroidism in pregnancy is a very commonly encountered issue in daily clinical practice. There is an obvious demand for universal screening and treatment with levothyroxine to reduce unwanted events. The aim of the study was to find out the association and autoimmunity among the newly detected hypothyroidism during pregnancy. Methods: This cross-sectional, observational study enrolled 175 pregnant women recruited by convenient sampling from the Department of Obstetrics and Gynecology, BIRDEM General Hospital, with or without diabetes. FT4 and thyroid autoantibodies were advised to those patients who had elevated TSH above the American Thyroid Association 2011-defined trimester-specific reference ranges. TSH, FT4, and anti-thyroid antibodies were tested using the chemiluminescent technique by the ADVIA centaur, Siemens. Data were analysed by SPSS version 25. Non-parametric tests were chosen for statistical analysis. Results: One hundred nineteen (68%) were found in second gravida or more and 56 (32%) were found in primigravida. Among the patients, 54 (30.9%) had a history of past abortion, 34 (19.4%) had a history of subfertility, and 28 (16%) had a family history of thyroid disease. Fifty (28.6%) of the pregnant women had thyromegaly. History of subfertility and a family history of thyroid disease and thyromegaly were significantly (p =.036, p <.001, p <.001) higher in hypothyroid group. TPO antibodies were positive in 69.6% of hypothyroid subjects. Conclusions: It is pertinent to do universal screening of all pregnant ladies including those with high risk factors for hypothyroidism in the first trimester of pregnancy to guide comprehensive management of hypothyroidism and improve the pregnancy outcomes. BIRDEM Med J 2024; 14(2): 87-92